The Implementation of Discovery-Based Learning in PAI Education Within the Framework of the Independent Curriculum at SDN 2 Marong - Sakarudin Sakarudin; Fathurrahmanmuhtar Fathurrahmanmuhtar (Sustainable, 2024)
The research is based on the Discovery Learning learning model applied to the independent curriculum. The purpose of this study is to describe how Islamic Religious Education educators apply the Discovery Learning learning model to Islamic religious education learning in the independent curriculum, and to find out the obstacles faced by Islamic Religious Education teachers when using the Discovery Learning learning model in class SDN 2 Marong central Lombok. The method used is a descriptive qualitative research method which is intended to explain and analyze events, social activities, actions, beliefs, and mindsets of a person both individually and in groups with the type of field research. Data were collected based on observation, interview and documentation techniques. Based on the findings of the research conducted by the author, the results show that: the application of the Discovery Learning learning model in Islamic Religious Education learning has shown the development of student participation in the learning process. There are three steps in the Discovery Learning learning model in Islamic religious education learning, namely: stimulation/giving stimulation, questions or identifying problems, and finally the conclusion has not been fully carried out by students properly as expected. However, there are obstacles faced by teachers in implementing the Discovery Learning learning model in Islamic religious education learning, including: lack of student learning motivation, lack of student learning activity, lack of student discipline and relatively short allocation of time and learning hours.